How strong is strong enough? - Stone, M.; Moire, G.
The purpose of this discussion is to describe the relationship between strength and 1) sports performance and 2) other variables contributing to athletic performance, particularly rate of force development and power. The discussion will be divided into two parts. Part One will deal with sports more oriented toward strength and power production and Part Two will consider sports requiring great endurance. - Introduction Part 1: Strength/Power Sports - Rank Order Studies - Correlational Studies - Longitudinal Studies - Summary Summary Evidence from a number of different types of research as well as observational data indicates that maximum strength is strongly related to sports performances that rely on speed and power. Although explaining performance in strength/power sports is a multi-factorial problem there is little doubt that maximum strength is a key component. Thus, it may be stated "you are never too strong".